Evaluación de la calidad del servicio de atención al usuario. Aplicación del modelo Servperf en el registro civil de Manta - Ecuador - Pico Meza, Evelyn Katherine (2024)
The main objective of public entities is to provide quality service to citizens, therefore, the evaluation of these services becomes one of the fundamental tools for evaluating the efficiency and effectiveness of these institutions, therefore, the The objective of this research is to propose activities to improve user service in the Civil Registry of Manta, for which, through the definition of the quality of the service from the citizen perspective and subsequently with the application of a validated evaluation model. The methodology applied was exploratory, descriptive and quantitative in nature, the data was obtained through the application of the Servperf quality evaluation model, which was analyzed based on the PLS-SEM structural equation model establishing the relationship of the observable variables and latent, this through the smartPLS4 statistical program. The results of the research indicated that the empathy dimension is directly related to user satisfaction.